Implementing Project Based Learning Using Google Sites to Enhance Students’ Travel Writing Abilities - Suharto, Ririn Pratiwi; Zubaidi, Zubaidi; Suryanto, Bambang; Setiawan, Ardian Wahyu; Putra, Dhony Manggala (PROJECT (Professional Journal of English Education), 2025)
This research explores the intersection of project-based learning (PBL) and technology-enhanced language education, specifically focusing on the implementation of PBL through Google Sites to enhance students’ travel writing skills. The research aims to evaluate both the implementation of PBL in travel writing and students’ perceptions of this learning model. Utilizing a case study methodology, data were collected through observations and questionnaires. English for Tourism Industry students were divided into four groups, each consisting of five students, and each group created one Digital Travel Writing project. Findings indicate that all groups effectively followed three key steps in the PBL process: project preparation, implementation, and evaluation. The resulting Digital Travel Writing projects focused on Central Java, Bali, East Java, and West Nusa Tenggara. Questionnaire responses indicated that most students enjoyed the PBL activities. In conclusion, the implementation of project-based learning using Google Sites was successful in enhancing students’ abilities in the Travel Writing course.